2020
DOI: 10.1130/g46650.1
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for fluid overpressure during hydrocarbon generation and expulsion from organic-rich shales

Abstract: Fluid overpressures are widely expected during hydrocarbon generation and expulsion from source rocks, yet direct evidence for this phenomenon is lacking in the case of organic-rich shales. Here we show that formation of bed-parallel fibrous calcite veins in mature laminated organic-rich shales in the Eocene Dongying depression, Bohai Bay Basin, east China, occurred in direct response to fluid overpressure due to hydrocarbon generation. The evidence for overpressure is recorded by coexisting primary aqueous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…Fluid inclusions directly record the paleofluid, and is the main method to study paleofluid activities (Wang et al, 2020). In this paper, fluid inclusion analysis was used to describe the fluid evolution of reservoir, and then to analyze the fluid activities in source rocks.…”
Section: Samples and Methodsmentioning
confidence: 99%
“…Fluid inclusions directly record the paleofluid, and is the main method to study paleofluid activities (Wang et al, 2020). In this paper, fluid inclusion analysis was used to describe the fluid evolution of reservoir, and then to analyze the fluid activities in source rocks.…”
Section: Samples and Methodsmentioning
confidence: 99%
“…Other diagenesis, such as hydrocarbon generation overpressure in shale, also belongs to positive diagenesis. The generated gas will make the laminated shales open more in the bed-normal direction, which favors incipient vein opening between laminae, even in the absence of deviatoric stress [3]. Veins filled with brittle minerals, such as quartz or calcite veins, are more conducive to the generation of fractured media, which is highly significant for the production of shale gas [4] and the immiscible two-phase flow (in oil zone with a gas cap) displacement [5].…”
Section: Introductionmentioning
confidence: 99%
“…These are the most commonly encountered structures in shales than in limestones in sedimentary basins around the globe (Chen, Steele‐MacInnis, Ge, Zhou, & Zhou, 2016; Cobbold, Zanella, Rodrigues, & Loseth, 2013). Previously, it was suggested that tectonics is responsible for the formation of fractures, in which the fibrous calcite veins are formed (e.g., Ma, Dong et al, 2016; M. Wang et al, 2018, 2020; Worden, Benshatwan, Potts, & Elgarmadi, 2015). While some authors argued that hydrocarbon generation is a key mechanism in the formation of fibrous sparry calcite (Cobbold et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While some authors argued that hydrocarbon generation is a key mechanism in the formation of fibrous sparry calcite (Cobbold et al, 2013). Fibrous sparry calcite is abundant in many shales worldwide (Cobbold et al, 2013; Cobbold, Zanella, Fourdan, Neraudeau, & Gouttefangeas, 2015; M. Wang et al, 2018, 2020; Zanella, Cobbold, & Boassen, 2015; Zanella, Cobbold, & Rojas, 2014; Zanella, Cobbold, Ruffet, & Leanza, 2015). According to Ramsay (1980), fibrous calcite is formed due to the crack‐seal mechanism.…”
Section: Introductionmentioning
confidence: 99%